The Development of Practice Evaluation Form Case Analysis and Problem Solving Electronical Control Automatic Transmission System - Satienchaiyakij, Paradorn; Chantakhad, Bhornsawan (Journal of Technical and Engineering Education, 2024)
Objective of this research was to 1) to development of practice evaluation form for analysis and problem solving electronical control automatic transmission system; and 2) study the results of using the practice evaluation form. The sample group was students in the Bachelor of Technology program. Mechanical major Kanchanaphisek Vocational College Nong Chok there were 12 people enrolled in the power transmission process course by selecting a purposive sample. The research procedures were as follows: 1) determine behaviour objectives by job analysis methods, 2) analysis behaviour objectives to determine evaluation point, 3) development of practice evaluation form, 4) analysis the intra and inter observer reliability, 5) evaluate practice work with a sample group and 6) evaluate the satisfaction of teachers and students. The research instruments included 1) the practice evaluation form, and 2) the satisfaction of teachers and students form on the evaluation process. The data were analysed using statistics 1) percentage, 2) mean, 3) standard deviation, 4) index of consistency, 5) content validity ratio, 6) pearson’s correlation coefficient 7) inter observer reliability and 8) Shapiro -Wilk test. The results of the research found that: 1) the practice evaluation form has 5 evaluation forms, with the reliability of the intra-observer being between .798 - .898 and inter observer being between .799 - .904, 2) the practice evaluation results were averaged 75.48%, 3) the satisfaction of the teachers with the evaluation process was in the very good level, the mean 4.13 and 4) the satisfaction of the samples with the evaluation process was in the good level, the mean 4.20